Battery cell, lithium ion battery comprising same and electronic equipment
By injecting the electrolyte with a one-and-injection scheme into the lithium iron phosphate energy storage battery cell and adding a composite reactive oxygen trapping agent to the two-injection electrolyte, the gas production and high-temperature performance problems of Li5FeO4 positive electrode lithium supplement agent are solved, and the gas production and high-temperature performance of Li5FeO4 positive electrode lithium supplement agent is achieved. Significant gas production improvement and high-temperature performance improvement.
Patent Information
- Application Number
- CN202411570613.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-05
AI Technical Summary
When Li5FeO4 is used as the positive lithium supplement agent in existing lithium iron phosphate energy storage batteries, there are problems such as severe gas production, poor circulation performance and poor high temperature stability.
The electrolyte is injected using a one- or two injection scheme, where the reactive oxygen trapping agent of the composite component, including vinyl sulfite and primary amine compounds or disulfide bond-containing compounds, to improve the gas production problem of the battery cell. and high temperature performance.
It significantly improves the gas production problem of the battery cell, improves the stability of high-temperature storage and high-temperature circulation performance, the gas production percentage is less than 13%, the recovery rate of high-temperature storage capacity can reach more than 97.3%, and the capacity retention rate of 500 cycles of high-temperature circulation can reach More than 95.8%.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to an electric core and a lithium ion battery and electronic equipment containing the same. Background Art
[0002] With the market demand for energy storage cells, the demand for long-life lithium iron phosphate energy storage cells is constantly growing. In order to further improve the long life of lithium iron phosphate energy storage cells, researchers in related fields are currently constantly exploring the technology of pre-lithiation of batteries.
[0003] The technologies for pre-lithiation of battery cells on the market mainly include positive electrode pre-lithiation and negative electrode pre-lithiation. Due to the high processing difficulty of negative electrode pre-lithiation and the difficulty in development due to factors such as existing equipment and processing environment, negative electrode pre-lithiation cannot be effectively implemented at present. At present, positive electrode pre-lithiation is mostly used in the market to pre-lithiate battery cells. Regarding positive electrode pre-lithiation, there are mainly two directions: lithium nickel-rich lithium supplement materials (chemical formula LiNiO2, referred to as LNO) and lithium iron-rich lithium supplement materials (chemical formula Li5FeO4, referred to as LFO). Among them, LNO lithium supplement materials are gradually being replaced by LFO lithium supplement materials due to their high prices. However, when LFO lithium supplement materials are used as lithium supplement agents, there is still a serious problem of gas production that needs to be solved urgently. Summary of the invention
[0004] In order to solve the serious gas generation problem and poor high temperature cycle performance and high temperature storage stability when LFO is used as a positive electrode lithium supplement in existing battery cells, the present invention provides a battery cell and a lithium ion battery and electronic device containing the same. The gas generation problem of the battery cell is significantly improved, and excellent high temperature cycle performance and high temperature storage stability can be achieved.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions.
[0006] In a first aspect, the present invention provides a battery cell, wherein the battery cell adopts a one-two injection scheme to inject electrolyte, and the electrolyte includes a one-injection electrolyte and a two-injection electrolyte;
[0007] The additive in the second electrolyte solution includes an active oxygen scavenger; the active oxygen scavenger includes a first component and a second component, the first component is vinyl sulfite, and the second component includes a primary amine compound and / or a disulfide bond-containing compound;
[0008] The positive electrode material layer in the positive electrode sheet of the battery cell includes lithium iron phosphate and a positive electrode lithium replenisher, and the positive electrode lithium replenisher includes Li5FeO4.
[0009] In a second aspect, the present invention provides a lithium-ion battery comprising the battery cell as described above.
[0010] In a third aspect, the present invention provides an electronic device comprising the lithium-ion battery as described above.
[0011] The positive and progressive effects of the present invention are:
[0012] The present invention aims at the serious gas generation problem and poor cycle performance and high temperature stability of lithium-ion batteries using LFO as a positive lithium supplement. The electrolyte is injected using a one-two injection scheme, and a composite active oxygen scavenger is added to the two-injection electrolyte. The obtained battery cell has the following advantages:
[0013] (1) The gas production problem has been significantly improved: after being stored at 60°C for 60 days, the gas production percentage can be lower than 13%, or even lower than 7%;
[0014] (2) Excellent high-temperature storage stability: After storage at 60°C for 60 days, the high-temperature storage capacity recovery rate can reach more than 97.3%, or even more than 97.7%;
[0015] (3) It also has excellent high-temperature cycle performance: the capacity retention rate after 500 cycles at 45°C can reach more than 95.8%, or even more than 97%. DETAILED DESCRIPTION
[0016] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0017] Battery Cell
[0018] In the battery cell provided in the first aspect of the present invention, the battery cell adopts a one-two injection scheme to inject electrolyte, and the electrolyte includes a one-injection electrolyte and a two-injection electrolyte;
[0019] The additive in the second electrolyte solution includes an active oxygen scavenger; the active oxygen scavenger includes a first component and a second component, the first component is vinyl sulfite, and the second component includes a primary amine compound and / or a disulfide bond-containing compound;
[0020] The positive electrode material layer in the positive electrode sheet of the battery cell includes lithium iron phosphate and a positive electrode lithium replenisher, and the positive electrode lithium replenisher includes Li5FeO4.
[0021] In some optional embodiments, the primary amine compound is selected from one or more of p-phenylenediamine, benzylamine, phenylethylamine, 1,2-phenylenediamine, propylenediamine and butylenediamine.
[0022] In some optional embodiments, the disulfide bond-containing compound is selected from one or more of lithium thiosulfate, lithium dithionate, lithium dithionite and lithium thiosulfate derivatives.
[0023] In some optional embodiments, the content of the active oxygen scavenger is 1.5%-9%, preferably 2%-8%, and more preferably 4%-6%, where the percentage is the mass percentage of the second electrolyte.
[0024] In some optional embodiments, the content of the vinyl sulfite is 1%-6%, for example, 2% or 4%, where the percentage is the mass percentage of the second electrolyte.
[0025] In some optional embodiments, the content of the primary amine compound is 0.5%-4%, for example, 2% or 3%, where the percentage is the mass percentage of the second electrolyte solution.
[0026] In some optional embodiments, the content of the disulfide bond-containing compound is 0.5%-4%, for example, 2%, where the percentage is the mass percentage of the second electrolyte solution.
[0027] In some preferred embodiments, the active oxygen scavenger is vinyl sulfite and a primary amine compound, and the mass ratio of the vinyl sulfite to the primary amine compound is 1:(0.2-3), preferably 1:(0.5-2), for example 1:1.
[0028] In some specific embodiments, the active oxygen scavenger is vinyl sulfite and p-phenylenediamine; the content of the vinyl sulfite is, for example, 4%, and the content of the p-phenylenediamine is, for example, 2%.
[0029] In some specific embodiments, the active oxygen scavenger is vinyl sulfite and benzylamine; the content of the vinyl sulfite is, for example, 4%, and the content of the benzylamine is, for example, 2%.
[0030] In some specific embodiments, the active oxygen scavenger is vinyl sulfite and phenethylamine; the content of the vinyl sulfite is, for example, 4%, and the content of the phenethylamine is, for example, 2%.
[0031] In some specific embodiments, the active oxygen scavenger is vinyl sulfite and 1,2-phenylenediamine; the content of the vinyl sulfite is, for example, 4%, and the content of the 1,2-phenylenediamine is, for example, 2%.
[0032] In some specific embodiments, the active oxygen scavenger is vinyl sulfite and propylene diamine; the content of the vinyl sulfite is, for example, 4%, and the content of the propylene diamine is, for example, 2%.
[0033] In some specific embodiments, the active oxygen scavenger is vinyl sulfite and dibutylene glycol; the content of the vinyl sulfite is, for example, 4%, and the content of the dibutylene glycol is, for example, 2%.
[0034] In some preferred embodiments, the active oxygen scavenger is vinyl sulfite and a disulfide bond-containing compound, and the mass ratio of the vinyl sulfite to the disulfide bond-containing compound is 1:(0.2-3), preferably 1:(0.5-2), for example 1:1.
[0035] In some specific embodiments, the active oxygen scavenger is vinyl sulfite and lithium thiosulfate; the content of the vinyl sulfite is, for example, 4%, and the content of the lithium thiosulfate is, for example, 2%.
[0036] In some specific embodiments, the active oxygen scavenger is vinyl sulfite and lithium dithionite; the content of the vinyl sulfite is, for example, 4%, and the content of the lithium dithionite is, for example, 2%.
[0037] In some preferred embodiments, the active oxygen scavenger is vinyl sulfite, a primary amine compound and a disulfide bond-containing compound, and the mass ratio of the vinyl sulfite, the primary amine compound and the disulfide bond-containing compound is 1:(0.5-1):(0.5-1), for example, 1:1:1.
[0038] In some specific embodiments, the active oxygen scavenger is vinyl sulfite, p-phenylenediamine and lithium thiosulfate; the content of the vinyl sulfite is, for example, 2%, the content of the p-phenylenediamine is, for example, 2%, and the content of the lithium thiosulfate is, for example, 2%.
[0039] In some optional embodiments, the lithium salt in the second electrolyte is selected from one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide.
[0040] In some specific embodiments, the lithium salt in the second electrolyte is lithium hexafluorophosphate.
[0041] In some optional embodiments, the solvent in the second electrolyte is selected from one or more of ethylene carbonate (EC), propylene carbonate, dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, propyl formate, propyl propionate and ethyl butyrate.
[0042] In some specific embodiments, the solvents in the second electrolyte are ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate, and the mass ratio of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate is, for example, 3:3:4.
[0043] In some optional embodiments, the additive in the second injection electrolyte further includes vinylene carbonate.
[0044] In some preferred embodiments, the content of vinylene carbonate is preferably 5%-12%, for example 10%.
[0045] In some preferred embodiments, the additives in the second-injection electrolyte further include fluoroethylene carbonate (FEC) and / or vinyl ethylene carbonate (VEC).
[0046] In some optional embodiments, the lithium salt in the first injection of electrolyte is selected from one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide.
[0047] In some specific embodiments, the lithium salt in the first injection of electrolyte is lithium hexafluorophosphate.
[0048] In some optional embodiments, the solvent in the electrolyte is selected from one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, propyl formate, propyl propionate and ethyl butyrate.
[0049] In some specific embodiments, the solvent in the one injection of electrolyte is ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate, and the mass ratio of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate is, for example, 3:3:4.
[0050] In some optional embodiments, the additive in the first injection of electrolyte is selected from one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC) and diethylene sulfate (DTD).
[0051] In some specific embodiments, the additives in the one injection of electrolyte are vinylene carbonate, fluoroethylene carbonate and vinyl sulfate, and the mass ratio of vinylene carbonate, fluoroethylene carbonate and vinyl sulfate is, for example, 3:1:1.
[0052] In some optional embodiments, the content of the lithium iron phosphate is greater than 93%, for example, 94%, where the percentage is the mass percentage of the positive electrode material layer.
[0053] In some optional embodiments, the content of Li5FeO4 is 0.5%-5%, for example, 3%, where the percentage is the mass percentage of the positive electrode material layer.
[0054] In some optional embodiments, the sum of the contents of the lithium iron phosphate and the Li5FeO4 is less than 98%, for example, 97%, where the percentage is the mass percentage of the positive electrode material layer.
[0055] In some optional embodiments, the positive electrode lithium supplement further includes LiNiO2.
[0056] In some preferred embodiments, the mass ratio of the Li5FeO4 to the LiNiO2 is (4-5):1.
[0057] In some embodiments, the preparation method of the battery cell includes the following steps: winding the positive electrode sheet, separator and negative electrode sheet stacked in sequence, injecting a shot of electrolyte, forming and aging, injecting a second shot of electrolyte, heat sealing and then dividing the volume to obtain.
[0058] In some preferred embodiments, the upper voltage limit of the formation is higher than 3.95V, preferably higher than 4.05V.
[0059] Positive electrode
[0060] In some optional embodiments, the positive electrode material layer further includes a binder.
[0061] The type of the binder is not particularly limited, and can be selected from polyvinylidene fluoride, polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid (PAA), ethylene-propylene-diene terpolymer and its sulfonate, styrene-butadiene rubber (SBR), fluororubber and various copolymers, such as PVDF.
[0062] In some optional embodiments, the content of the binder is 1%-10%, for example, 1.5% or 1.8%, where the percentage is the percentage of the total mass of the positive electrode material layer.
[0063] In some optional embodiments, the positive electrode material layer further includes a conductive agent.
[0064] The type of the conductive agent is not particularly limited, and is a reagent used to ensure that the electrode has good charge and discharge performance. It can be selected from graphite materials such as natural graphite and artificial graphite, carbon black SP, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black and other carbon black materials, carbon fibers, metal fibers and other conductive fibers, metal powders such as carbon fluoride powder, aluminum powder, nickel powder and other metal powders, zinc oxide, potassium titanate and other conductive whiskers, and titanium dioxide and other conductive metal oxides or polyphenylene derivatives.
[0065] In a specific embodiment, the conductive agent is conductive carbon SP.
[0066] In some optional embodiments, the content of the conductive agent is 0.2%-3%, for example, 0.75% or 1.2%, where the percentage is the percentage of the total mass of the positive electrode material layer.
[0067] In some specific embodiments, in the positive electrode material layer, the mass ratio of the lithium iron phosphate, the lithium supplement agent, the conductive agent and the binder is 94:3:1.2:1.8.
[0068] In the present invention, the positive electrode sheet of the battery cell includes a positive electrode current collector, and the positive electrode material layer is arranged on at least one surface of the positive electrode current collector.
[0069] Wherein, the positive electrode current collector may be a conventional positive electrode current collector in the art. The positive electrode current collector is a substrate supporting the positive electrode material layer, usually a metal foil with a thickness of 3-500 microns. There is no particular restriction on the material, as long as it has high conductivity and does not produce chemical reactions in the secondary battery system. For example, it can be a foil formed after surface treatment of nickel, titanium, aluminum, nickel, silver, stainless steel, carbon, etc. The positive electrode current collector usually has a smooth surface, but fine lines can also be formed on its surface to increase the adhesion between the positive electrode material layer and the positive electrode current collector. In addition to the foil, the positive electrode current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric. Generally, the positive electrode current collector is aluminum foil.
[0070] In some embodiments, the preparation method of the positive electrode sheet includes: fully stirring and mixing the components of the positive electrode material layer in a solvent to obtain a positive electrode slurry, coating it on at least one surface of the positive electrode collector, drying it, and rolling and compacting it.
[0071] In some optional embodiments, the solvent includes one or more of N-methylpyrrolidone (NMP), dimethyl carbonate, ethylene carbonate and diethylene carbonate, for example, NMP.
[0072] Negative plate
[0073] In the present invention, the negative electrode sheet in the battery cell comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector.
[0074] In the present invention, the negative electrode active material in the negative electrode material layer may be a conventional negative electrode active material of a lithium ion battery in the art. The negative electrode active material of the lithium ion battery may use a compound that can reversibly embed and deintercalate lithium. Specific examples include but are not limited to: carbon materials such as crystalline carbon (natural graphite and artificial graphite, etc.), amorphous carbon, carbon-coated graphite and resin-coated graphite, or oxide materials such as indium oxide, silicon oxide, tin oxide, lithium titanate, zinc oxide, lithium oxide, etc., or lithium metal or a metal material that can form an alloy with lithium; wherein the metal material that can form an alloy with lithium is, for example, Cu, Sn, Si, Co, Mn, Fe, Sb and Ag. Binary or ternary alloys containing these metals and lithium may also be used as negative electrode active materials. These negative electrode active materials may be used alone or in combination of two or more. From the perspective of high energy density, carbon materials such as graphite may also be used in combination with Si, Si alloys, Si oxides and other Si-based materials.
[0075] In some embodiments, the negative electrode active material includes any one of soft carbon, hard carbon, artificial graphite, natural graphite, silicon, silicon oxides, silicon carbon compounds, or lithium titanate, or a combination of at least two thereof.
[0076] In one specific embodiment, the negative electrode active material is artificial graphite.
[0077] In some embodiments, the negative electrode material layer further includes a thickener.
[0078] The addition of the thickener can increase the system viscosity of each component in the negative electrode slurry, and can be a thickener conventionally used in the art for preparing negative electrode sheets, such as sodium carboxymethyl cellulose (CMC).
[0079] In some embodiments, the negative electrode material layer further includes a conductive agent.
[0080] There are no particular restrictions on the conductive agent, as long as it has conductivity and does not cause chemical changes in the battery. For example, the conductive agent may be: graphite, such as natural graphite or artificial graphite; carbon-based materials, such as carbon black (Super P), acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black or carbon fiber; metal powder or metal fiber, such as copper, nickel, aluminum or silver; conductive whiskers, such as zinc oxide whiskers or potassium titanate whiskers; conductive metal oxides, such as titanium dioxide; or conductive polymers, such as polyphenylene derivatives.
[0081] In some embodiments, the negative electrode material layer further includes a binder.
[0082] The type of the binder is not particularly limited, and can be selected from polyvinylidene fluoride, polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid (PAA), ethylene-propylene-diene terpolymer and its sulfonate, styrene-butadiene rubber (SBR), fluororubber and various copolymers, such as PAA and SBR.
[0083] In some specific embodiments, in the negative electrode material layer, the mass ratio of the negative electrode active material, the conductive agent, the binder and the thickener is 97.2:0.5:1.8:0.5.
[0084] In the present invention, the negative electrode current collector may be a conventional negative electrode current collector in the art. The negative electrode current collector is used as a substrate to support the negative electrode material layer, and is generally a metal foil having a thickness of 3-500 microns. There is no particular restriction on the material, as long as it has high conductivity and does not produce chemical reactions in the secondary battery system. For example, it can be a foil formed after surface treatment of nickel, titanium, aluminum, nickel, silver, stainless steel, carbon, etc. The negative electrode current collector is generally a smooth surface, but fine lines may also be formed on its surface to increase the adhesion between the negative electrode material layer and the negative electrode current collector. In addition to the foil, the negative electrode current collector may also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric. Generally, the negative electrode current collector is copper foil.
[0085] In some embodiments, the method for preparing the negative electrode sheet comprises the following steps: thoroughly stirring and mixing the components of the negative electrode material layer in a solvent to obtain a negative electrode slurry which is applied on at least one surface of the negative electrode current collector, dried, cold pressed, and cut.
[0086] Diaphragm
[0087] In the present invention, the separator in the battery cell may be a separator conventionally used in the art.
[0088] In some optional embodiments, the separator may be a polypropylene film or a polyethylene film.
[0089] Wherein, the air permeability of the diaphragm may be 180-380 s / 100mL.
[0090] Wherein, the porosity of the diaphragm may be 30%-50%.
[0091] Wherein, the thickness of the diaphragm may be 9-18 μm.
[0092] In a specific embodiment, the diaphragm is a polyethylene film; the thickness of the diaphragm is 11 μm; the air permeability of the diaphragm is 230 s / 100 mL; and the porosity of the diaphragm is 40%.
[0093] Lithium-ion battery
[0094] The lithium ion battery provided in the second aspect of the present invention comprises the battery cell as described above.
[0095] In the present invention, the lithium-ion battery is generally a square hard-shell battery, a soft-pack battery and a cylindrical battery.
[0096] In the present invention, the lithium ion battery can be prepared by conventional methods in the art.
[0097] Electronic devices
[0098] The electronic device provided in the third aspect of the present invention comprises the lithium-ion battery as described above.
[0099] Exemplarily, the electronic device described in the present invention may be, but is not limited to, mobile devices (such as mobile phones, tablet computers, laptop computers, video recorders, portable printers / copiers, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems and backup power supplies, etc.
[0100] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention. The present invention is further illustrated by way of examples below, but the present invention is not limited to the scope of the embodiments described. The experimental methods in the following examples that do not specify specific conditions are selected according to conventional methods and conditions, or according to the product specifications. Unless otherwise specified, the reagents and raw materials used in the present invention are commercially available.
[0101] Example 1
[0102] The preparation of the battery cell includes the following steps:
[0103] (1) Preparation of positive electrode sheet: The positive electrode active materials lithium iron phosphate, polyvinylidene fluoride (PVDF), conductive carbon SP, and lithium supplement agent LFO are mixed evenly in a solvent NMP (45 parts by mass) at a mass ratio of lithium iron phosphate: PVDF: conductive carbon SP: lithium supplement agent LFO = 94:1.8:1.2:3 (a total of 100 parts by mass), and the resulting slurry is coated on an aluminum foil and dried to obtain a positive electrode sheet.
[0104] (2) Preparation of negative electrode sheet: The negative electrode active materials artificial graphite, polyacrylic acid (PAA), CMC, conductive carbon SP, and SBR are mixed evenly in a solvent deionized water (50 parts by mass) in a mass ratio of graphite: PAA: CMC: conductive carbon SP: SBR = 97.2:1.3:0.5:0.5:0.5, and the resulting slurry is coated on a copper foil and dried to obtain a negative electrode sheet.
[0105] (3) Preparation of electrolyte: In an argon atmosphere glove box with oxygen and water content less than 1 ppm, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) were mixed in a mass ratio of 3:3:4 to obtain a mixed solvent. 1 mol / L lithium hexafluorophosphate was added as a conductive salt to the mixed solvent and dissolved and mixed evenly to obtain an initial salt solution without additives.
[0106] Preparation of an electrolyte: Add additives to the initial salt solution: vinylene carbonate (VC, content is 3%), fluoroethylene carbonate (FEC, content is 1%) and diethylene sulfate (DTD, content is 1%), mix well to obtain an electrolyte.
[0107] Preparation of the second electrolyte: Add additives to the initial salt solution: vinylene carbonate (VC, content is 10%) and active oxygen scavenger; wherein the active oxygen scavenger is vinyl sulfite (ES, content is 4%) and p-phenylenediamine (content is 2%), mix well to obtain the second electrolyte.
[0108] (4) Production of battery cells: The positive electrode sheets, separators and negative electrode sheets stacked in sequence are wound into battery cells, which are packaged with aluminum plastic film. The battery cell capacity is designed to be 40Ah. A total of 119g of electrolyte is injected. After formation and aging, the upper limit voltage of the formation is 4.1V. A total of 21g of electrolyte is injected. After heat sealing, the capacity is divided to obtain a battery cell. Among them, the separator is a polyethylene film; the thickness of the separator is 11μm; the air permeability of the separator is 230s / 100mL; and the porosity of the separator is 40%.
[0109] Embodiment 2-6
[0110] The only difference between Example 2-6 and Example 1 is that benzylamine, phenylethylamine, 1,2-phenylenediamine, propylenediamine and butylenediamine are used to replace p-phenylenediamine in the two injections of electrolyte, and the other conditions are the same as those in Example 1.
[0111] Embodiment 7-8
[0112] The only difference between Example 7-8 and Example 1 is that lithium thiosulfate and lithium dithionite are used in the two injections of electrolyte to replace p-phenylenediamine, and the other conditions are the same as those in Example 1.
[0113] Examples 9-10
[0114] The only difference between Examples 9-10 and Example 1 is that the upper limit voltages of the formation are 4.2V and 3.95V respectively, and the other conditions are the same as those of Example 1.
[0115] Embodiment 11
[0116] The only difference between Example 11 and Example 1 is that in the second injection of electrolyte, the content of vinyl sulfite is 2%, and the content of p-phenylenediamine is 5%. The other conditions are the same as those in Example 1.
[0117] Example 12
[0118] The only difference between Example 12 and Example 1 is that in the second injection of electrolyte, the content of vinyl sulfite is 6%, and the content of p-phenylenediamine is 3%. The other conditions are the same as those in Example 1.
[0119] Embodiment 13
[0120] The only difference between Example 13 and Example 1 is that in the two injections of electrolyte, the content of vinyl sulfite is 1%, and the content of p-phenylenediamine is 0.5%. The other conditions are the same as those in Example 1.
[0121] Embodiment 14
[0122] The only difference between Example 14 and Example 1 is that in the two injections of electrolyte, the active oxygen scavengers are vinyl sulfite (content is 2%), p-phenylenediamine (content is 2%) and lithium thiosulfate (content is 2%), and the other conditions are the same as in Example 1.
[0123] Embodiment 15
[0124] The only difference between Example 15 and Example 1 is that the lithium supplement is LFO and LNO, the mass ratio of lithium iron phosphate, PVDF, conductive carbon SP, lithium supplement LFO and LNO is 94:1.5:0.75:3:0.75 (100 parts by mass in total), and the other conditions are the same as Example 1.
[0125] Comparative Example 1
[0126] The difference between this comparative example and Example 1 is that no active oxygen scavenger is used in the second injection of electrolyte, and the other conditions are the same as those in Example 1.
[0127] Comparative Example 2
[0128] The difference between this comparative example and Example 1 is that in the second injection of electrolyte, the active oxygen scavenger is only p-phenylenediamine (content is 2%), and there is no vinyl sulfite. The other conditions are the same as those in Example 1.
[0129] Comparative Example 3
[0130] The difference between this comparative example and Example 1 is that in the second injection of electrolyte, the active oxygen scavenger is only vinyl sulfite (content is 4%), without p-phenylenediamine, and the other conditions are the same as those in Example 1.
[0131] Comparative Example 4
[0132] The difference between this comparative example and Example 1 is that in the second injection of electrolyte, the active oxygen scavenger is only p-phenylenediamine (content is 6%), and there is no vinyl sulfite. The other conditions are the same as those in Example 1.
[0133] Comparative Example 5
[0134] The difference between this comparative example and Example 1 is that in the second injection of electrolyte, the active oxygen scavenger is only vinyl sulfite (content is 6%), without p-phenylenediamine, and the other conditions are the same as those in Example 1.
[0135] Comparative Example 6
[0136] The only difference between this comparative example and Example 14 is that in the two injections of electrolyte, the active oxygen scavengers are p-phenylenediamine (content is 2%) and lithium thiosulfate (content is 2%), and there is no vinyl sulfite. The other conditions are the same as Example 14.
[0137] Effect Example 1
[0138] The gas production and capacity performance of the battery cells obtained in Examples 1-15 and Comparative Examples 1-6 were tested:
[0139] (1) Gas production percentage and high temperature storage capacity recovery rate
[0140] The obtained battery cells were subjected to a storage test at a high temperature of 60°C to test the capacity recovery rate and gas production of the battery cells after 60 days. The specific steps are as follows:
[0141] The initial volume of the battery cell is V0. After being stored at 60°C for 60 days, the battery cell volume is V1. The gas production percentage of the battery cell is (V1-V0) / V0.
[0142] After the capacity test of the battery cell, the initial capacity is defined as C0. The fully charged battery cell is stored at 60°C for 60 days. Then the battery cell is charged and discharged with a small current for three cycles. The capacity of each cycle is tested and the average value of the three cycles is C1. The value of C1 / C0 is the high temperature storage capacity recovery rate.
[0143] The above test results are shown in Table 1.
[0144] (2) High temperature cycle capacity retention rate
[0145] Test the capacity retention rate of the battery cell 1P / 1P after 500 cycles at 45°C. The specific test steps are as follows:
[0146] At 45°C, after 3 cycles of activation at 0.33C, charge to 80% SOC at 1C, charge 80%-100% SOC (3.65V) at 0.33C, and discharge to 2.5V at 1C. The capacity of the first cycle using this process is C 初 After 500 cycles of this process, the capacity is C n ; The capacity retention rate after 500 cycles at room temperature is C n / C 初 ×100%. The test results are shown in Table 1.
[0147]
[0148] As can be seen from Table 1, the present invention adopts a one-two injection scheme to inject electrolyte on the basis of LFO lithium supplement, and adds a composite component of active oxygen scavenger to the two-injection electrolyte. The gas production problem of the obtained battery cell is significantly improved and excellent high-temperature cycle performance and high-temperature storage stability can be taken into account. Specifically, after storage at 60°C for 60 days, the gas production percentage can be lower than 13%, or even lower than 7%; after storage at 60°C for 60 days, the high-temperature storage capacity recovery rate can reach more than 97.3%, or even more than 97.7%; the capacity retention rate of 500 cycles at 45°C can reach more than 95.8%, or even more than 97%.
[0149] In comparative examples 1-6, no active oxygen scavenger is used, or the first component or the second component is used alone as an active oxygen scavenger. Compared with the composite active oxygen scavenger including the first component and the second component in Examples 1-15 of the present invention, the percentage of gas production, the recovery rate of high-temperature storage capacity and the retention rate of high-temperature cycle capacity are all relatively poor. This may be because the vinyl sulfite as the first component absorbs active oxygen and is oxidized to vinyl sulfate, and then the vinyl sulfate continues to undergo a film-forming reaction at the negative electrode; on the basis of the first component, after the primary amine compound as the second component captures active oxygen, a nitrogen-containing and oxygen-containing compound will be generated. The compound often has a lower delithiation barrier and can also achieve the effect of ensuring the lithium ion transmission capacity. The synergistic effect with the film-forming product of vinyl sulfate can ensure both the high-temperature stability of the interface and the excellent ion conductivity, and finally effectively improve the cycle performance. The disulfide bond-containing compound as the second component can, on the basis of the first component, coordinately regulate and repair the damaged SEI film after the cycle, making the SEI film more stable and the inorganic component proportion higher, ensuring the excellent lithium ion transmission capacity at the interface, thereby effectively improving the cycle performance. However, when the first component or the second component alone is used as an active oxygen scavenger, it cannot effectively exert a synergistic effect and cannot achieve the above-mentioned effect. Specifically:
[0150] Compared with Example 1, no active oxygen scavenger was used in the second injection electrolyte of Comparative Example 1. After being stored at a high temperature of 60°C for 60 days, the gas production percentage increased significantly to 29.2%. The gas production problem was serious, and the high-temperature storage capacity recovery rate and high-temperature cycle capacity retention rate were significantly reduced.
[0151] Compared with Example 1, in the two-injection electrolyte of Comparative Examples 3 and 5, the active oxygen scavenger is only the first component of vinyl sulfite (content is 4% and 6% respectively), without the second component. After being stored at a high temperature of 60°C for 60 days, the gas production percentage, high temperature storage capacity recovery rate and high temperature cycle capacity retention rate are significantly deteriorated, and the high temperature stability is poor. Even if the amount of vinyl sulfite in Comparative Example 5 is as high as 6%, although the gas production percentage is reduced by about 3%, the gas production problem is still very serious compared with the embodiments of the present application, and the high temperature storage stability and high temperature cycle performance are also poor.
[0152] Compared with Example 1, in the two-injection electrolyte of Comparative Examples 2 and 4, the active oxygen scavenger only contains the second component (p-phenylenediamine, the content is 2% and 6% respectively), without the first component. After being stored at a high temperature of 60°C for 60 days, the gas production percentage is significantly increased, and the high temperature storage capacity recovery rate and high temperature cycle capacity retention rate are also deteriorated to varying degrees. Even if the amount of active oxygen scavenger used in Comparative Example 4 is 6%, compared with the embodiments of the present application, not only the gas production problem is not improved, but the high stability and cycle performance are still poor.
[0153] Compared with Example 14, in the second injection electrolyte of Comparative Example 6, the active oxygen scavenger only contains the second component (p-phenylenediamine and lithium thiosulfate) and does not contain the first component. After storage at a high temperature of 60°C for 60 days, the gas production percentage increases significantly, the gas production problem is serious, and the high-temperature storage capacity recovery rate and the high-temperature cycle capacity retention rate are significantly reduced.
[0154] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A battery cell, characterized in that: The battery cell adopts a one-two injection scheme to inject electrolyte, and the electrolyte includes a first injection electrolyte and a second injection electrolyte; The additive in the second electrolyte solution includes an active oxygen scavenger; the active oxygen scavenger includes a first component and a second component, the first component is vinyl sulfite, and the second component includes a primary amine compound and / or a disulfide bond-containing compound; The positive electrode material layer in the positive electrode sheet of the battery cell includes lithium iron phosphate and a positive electrode lithium replenisher, and the positive electrode lithium replenisher includes Li5FeO4.
2. The battery cell according to claim 1, characterized in that: The primary amine compound is selected from one or more of p-phenylenediamine, benzylamine, phenylethylamine, 1,2-phenylenediamine, propylenediamine and butylenediamine.
3. The battery cell according to claim 1, characterized in that: The disulfide bond-containing compound is selected from one or more of lithium thiosulfate, lithium dithionate, lithium dithionite and lithium thiosulfate derivatives.
4. The battery cell according to claim 1, characterized in that: The second electrolyte injection meets one or more of the following conditions ad: a. The content of the active oxygen scavenger is 1.5%-9%, where the percentage is the mass percentage of the two electrolyte injections; b. The content of the vinyl sulfite is 1%-6%, and the percentage is the mass percentage of the second electrolyte solution; c. The content of the primary amine compound is 0.5%-4%, where the percentage is the mass percentage of the two electrolytes; d. The content of the disulfide bond-containing compound is 0.5%-4%, and the percentage is the mass percentage of the two injections of electrolyte.
5. The battery cell according to claim 1, characterized in that: The active oxygen scavenger is vinyl sulfite and a primary amine compound, and the mass ratio of the vinyl sulfite to the primary amine compound is 1:(0.2-3); Alternatively, the active oxygen scavenger is vinyl sulfite and a disulfide bond-containing compound, and the mass ratio of the vinyl sulfite to the disulfide bond-containing compound is 1:(0.2-3); Alternatively, the active oxygen scavenger is vinyl sulfite, a primary amine compound and a disulfide bond-containing compound, and the mass ratio of the vinyl sulfite, the primary amine compound and the disulfide bond-containing compound is 1:(0.5-1):(0.5-1).
6. The battery cell according to claim 1, characterized in that: The second electrolyte injection meets one or more of the following conditions ac: a. The lithium salt in the second electrolyte is selected from one or more of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide; b. The solvent in the second electrolyte is selected from one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, propyl formate, propyl propionate and ethyl butyrate; c. The additives in the second electrolyte solution also include vinylene carbonate.
7. The battery cell according to claim 1, characterized in that: The electrolyte injection satisfies one or more of the following conditions ac: a. The lithium salt in the electrolyte is selected from one or more of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide; b. The solvent in the electrolyte is selected from one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, propyl formate, propyl propionate and ethyl butyrate; c. The additive in the electrolyte is selected from one or more of vinylene carbonate, fluoroethylene carbonate and vinyl sulfate.
8. The battery cell according to claim 1, characterized in that: The positive electrode material layer satisfies one or more of the following conditions ad: a. The content of the lithium iron phosphate is greater than 93%, where the percentage is the mass percentage of the positive electrode material layer; b. The content of Li5FeO4 is 0.5%-5%, where the percentage is the mass percentage of the positive electrode material layer; c. The sum of the contents of the lithium iron phosphate and the Li5FeO4 is less than 98%, where the percentage is the mass percentage of the positive electrode material layer; d. The positive electrode lithium supplement also includes LiNiO2.
9. A lithium ion battery, characterized in that: It comprises the battery cell as claimed in any one of claims 1 to 8.
10. An electronic device, characterized in that: It comprises the lithium ion battery as claimed in claim 9.
Citation Information
Patent Citations
High-temperature plugging agent system used for heavy-oil thermal recovery oil reservoir
CN108531159A
High-performance electrolyte and lithium ion battery containing same
CN115360427A
Lithium ion battery electrolyte and application thereof
CN118693348A
Nonaqueous electrolyte solution for battery and nonaqueous electrolyte solution battery equipped with it
JP2008112681A
Nonaqueous electrolyte and power storage device including the same
JP2016134283A
Cited By
Wide-temperature-range lithium ion battery electrolyte as well as preparation method and application thereof
CN120127216A